Social and eonomic foundations of community education for peace in Islam - Ambali, Taiwo T. (Department of Theology and Philosophy, Faculty of Islamic Studies, Universiti Kebangsaan Malaysia, 2017)
This article highlights and discusses propositions in hadith and the Holy Quran could form social and economic bases of adult community education curriculum designed for the promotion of peace in Nigeria and the world. The paper is evoked by three interrelated reasons. First, in recent times violence appears to be springing up and spreading intractably in the world and especially in Nigeria which begs for sustainable solution. Second, while Islam is a religion of peace, there is wide misconception pointing to the contrary with the act of violence seemingly prevalent in Muslim dominated areas or perhaps being perpetuated by not well informed Muslims. Third, architects of violence in most instances are both educated and uneducated who may need to de-learn and re-learn Islamic position on promotion of peace through adult community education. Following the discussion, the paper draws implications for the development of relevant peace education curriculum and mode of delivery.